Бесы: [роман] / Федор Достоевский - Достоевский Федор Михайлович (Всемирная литература, 2017)
Экземпляры: ф.6 (20190613) / Инвентарный номер: 2624 И / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Д 70 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1-44